Comparing reading processing strategies of second language readers - Mohd Shah, Parilah; Yusof, Aminuddin; Mohamed Lip, Suhana; Mahmood, Nurulhafizah; Abd Hamid, Yurni Emilia; M. Hashim, Shahirah (Science Publications, 2010)
Problem statement: The message that a writer tries to convey in a text would be subjected to several interpretations by readers. Apparently, reading is a complex process of getting input. A well-known researcher offers two views of reading: (i) reading is a process of decoding written symbols and (ii) reading is a process of reconstructing meaning. It has also been proposed that readers used reading processing strategies in the process of understanding text. Most language educators are not aware of the specific reading strategies that second language readers utilize. Therefore, it is deemed necessary to conduct a study that could explore the specific types of strategies used and to compare the strategies utilized by readers of differing abilities. Approach: A study is conducted to examine the second language readers' use of reading strategies at the Malaysian secondary schools. They read a piece of reading material, and then respond to questionnaires concerning reading strategies such as supervising strategies, support strategies and paraphrase strategies. Results: The findings indicate that there are differences in reading strategies used by second language readers of differing abilities for some of the question items. The results suggest the need to address the incorporation of reading strategy instruction in the language curriculum in order to produce more efficient readers. Conclusion: This investigation is another useful contribution to the applied linguistics research since second language educators would gain better insight into the readers comprehension process.